Government or governance of urban innovation? A tale of two cities. - Dente, Bruno; Bobbio, Luigi; Spada, Alessandra (TH Zürich, ORL-Institut, 2005)
Anhand der institutionellen und politischen Entwicklungen des letzten Jahrzehnts in den beiden norditalienischen Großstädten Mailand und Turin untersuchen die Autoren den Zusammenhang zwischen städtischen Innovationen und neuen Formen einer Urban Governance. Ausgehend von der Theorie des Sozialkapitals und der neueren Institutionentheorie wird der Hypothese nachgegangen, dass je vielfältiger die beteiligten Akteure und je dichter ihre Verknüpfung im Netzwerk ist, desto besser sei die innovative Leistung. Die Untersuchungen zeigen, dass Turin eine eindeutig höhere Innovationsleistung erbracht hat als Mailand , dies aber wesentlich auf traditionelle Weise, nämlich durch die Führungsrolle der politischen Institutionen, zurückzuführen sei. Demgegenüber ist Mailand zwar weniger innovativ, aber darin moderner, als es den Forderungen der Zivilgesellschaft wesentlich weiter nachkommt. oc/difu

The article discusses the relationship between urban innovation and new forms of governance. In the study, the authors derive from the existing literature on social capital and institutional development, the hypotheses that the more diverse the actors involved and the tighter their linkages, the better the innovative performance will be. In order to test these hypotheses, two northern Italian cities, Milan and Turin, that underwent similar changes in the political and institutional sphere in the decade 1993-2002, has been investigated. The research carried out shows that certainly Turin had a better performance in terms of urban innovation than Milan and that such a result is associated with a more complex network in which different levels of government, and different types of actors, are represented. Also the "tightness" of the network is higher, thus providing evidence to support the idea that policy innovation is associated with changes in the structure of governance. However, looking in more detail at the evidence collected, it reveals quite clearly that Milan is much more receptive to the proposals coming from civil society (both from the profit and the non-profit sector) while Turin, like other innovative Italian cities, seems much more dependent upon the leadership of the public institutions. difu
Keywords: Stadtentwicklungsplanung; Innovation; Planungstheorie; Strukturwandel; Kooperation; Stadtgesellschaft; Stadtentwicklungspolitik; Kreativität; Zivilgesellschaft; Public-Private-Partnership; Städtevergleich; Urban Governance; Local Governance; Institutionentheorie; Sozialkapital